Curriculum Development Strategy Based on Outcome Based Education (OBE) to Improve the Quality of Education in Higher Education - Ali, Ridwan; Jamin, Hanifuddin (Academia Publication, 2025)
The aim of this study is to examine the fundamental concepts of Outcome-Based Education (OBE), strategies for developing an OBE-based curriculum, the challenges of its implementation, and its impact on the quality of higher education. This research employs a descriptive qualitative approach using the library research method. Through a literature review, the author analyzes various academic sources and relevant national policies. The findings indicate that OBE emphasizes measurable learning outcomes, active student participation, and the integration of learning with the needs of the workforce. Effective implementation strategies include formulating graduate profiles, developing learning outcomes, designing syllabi and lesson plans (RPS) based on outcomes, and involving external stakeholders. Despite facing several challenges such as resistance to change, limited human resources, and inadequate infrastructure, OBE has proven to enhance graduate competitiveness, study program accreditation, and student engagement in the learning process. Therefore, the OBE approach is recommended as a foundational framework in curriculum development to address the future challenges of higher education.